Perancangan Kerangka Belakang Mobil Minimalis Roda Tiga - Muhammad Rifai; Wahyudi Wahyudi; Tri Andi Setiawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
Minimalist car three-wheeled car is a new innovation made to maximize vehicle use. Indesigning a separate three-wheeled minimalist car, it will combine the trike tilting system where whenturning the car body will tilt towards the turn. One of the main components of a car that is veryimportant is the chassis. Chassis is one of the important parts in a car that must have strongconstruction to withstand vehicle loads. The purpose of this research is to find out the minimalistthree-wheeled car chassis design that is expected to become a modern vehicle.In this study using thedevelopment method by using Solidworks software as a software for creating Arm designs. The use ofSolidworks software also aims to perform numerical analysis to determine the strength of the chassisby looking at the results of von mises stress on the results of software analysis. In numerical analysisthe chassis uses three tests with different load variations, namely, the load is evenly distributed on thesurface, the load is centered on the center of gravity, and the load when the collision occurs.From theexisting design, the concept of the three of the three concepts was chosen because it was able towithstand the load even with profiles and dimensions with a maximum load of 8773,735. In the designof Swing Arm using ASTM A36 pipe material with yield strenght of 250 N / mm2. In the validation ofthe swing arm strength using the safety factor of 4. So the validation uses a permit voltage of 62.5 N /mm2. From the validation between the analysis carried out by the chassis, it was declared safebecause the voltage that occurred in the chassis did not exceed the allowable voltage.